Silicon-based thermal insulation material and preparation method thereof
By preparing a silicon-based thermal insulation material containing chitosan/multi-walled carbon nanotubes/ATO composite material, the problem of insufficient mechanical strength caused by the incompatibility of tin antimony oxide ATO and the original matrix material in the existing technology is solved, and the problem of insufficient mechanical strength is solved. The material has good thermal insulation properties and durability.
Patent Information
- Application Number
- CN202411431098.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-14
AI Technical Summary
In the prior art, tin oxide antimony ATO is embedded in graphene aerosol for infrared absorption, and it is incompatible with the original matrix material, resulting in insufficient mechanical strength after spraying.
A silicon -based thermal insulation material includes its composition includes benzalcopic lotion, potassium silicate, nano ceramic micro beads, vermiculite, silicon dioxide gel, shell glycogen/multi -layer carbon nanotuba/ATO composite material, etc., etc. Through specific mixing and stirring steps, it is formed to form materials with good thermal insulation performance and durability.
The improvement of the good thermal insulation performance and mechanical performance of the material, especially the use of the shell/multi -layer carbon nanotuba/ATO composite material, improves the durability of the material, and can be determined in the 700 -hour durable climate aging. Can't be foaming, not peeling, no cracks.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sound insulation materials, and in particular relates to a silicon-based insulation material and a preparation method thereof. Background Art
[0002] In the construction sector, sound insulation materials are widely used on walls, ceilings and floors to effectively isolate noise and provide a quiet environment for living and working spaces. In industrial environments, such materials help reduce the noise generated by mechanical operations, thereby improving working conditions for employees.
[0003] At the same time, in the construction field, sound insulation materials can effectively reduce indoor and outdoor heat exchange, reduce the use of air conditioning and heating, improve the comfort of living or working environment while reducing energy consumption.
[0004] In the prior art, antimony tin oxide (ATO) is embedded in graphene aerosol for infrared absorption, and then further applied to wall materials. However, the aerosol is incompatible with the original matrix material, resulting in insufficient mechanical strength after spraying. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a silicon-based thermal insulation material.
[0006] The present invention is achieved through the following technical solutions:
[0007] A silicon-based thermal insulation material, which is composed of the following components by mass: 70-80 parts of styrene-acrylic emulsion, 5-7 parts of potassium silicate, 10-12 parts of nano-ceramic microbeads, 10-12 parts of vermiculite, 7-9 parts of silicon dioxide aerogel, 8-16 parts of chitosan / multilayer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8-10 parts of propylene glycol methyl ether, 30-40 parts of water, 1-3 parts of hydroxymethyl cellulose, and 1-2 parts of 0.5 mol / L ammonia aqueous solution;
[0008] The molecular weight of the chitosan is 310000-375000 Da.
[0009] Preferably, the chitosan / multi-layer carbon nanotube / ATO composite material has an amount of 12 to 16 parts. Further, the chitosan / multi-layer carbon nanotube / ATO composite material has an amount of 16 parts.
[0010] Furthermore, the preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is as follows: dissolve chitosan in an acetic acid aqueous solution; then add multi-layer carbon nanotubes and ATO, and then ultrasonicate for 2 hours until the suspension becomes uniform, centrifuge, and dry at 50°C for 24 hours to obtain. The multi-layer carbon nanotubes have an average length of 10 μm and an average diameter of 12 nm. The average particle size of the ATO is <50 nm. The thermal conductivity of the silicon-based thermal insulation material is 0.0320~0.0412 Wm -1 K -1 The silicon-based thermal insulation material does not bubble, peel or crack when subjected to an artificial weathering aging resistance test for more than 700 hours.
[0011] The present invention also provides a method for preparing a silicon-based thermal insulation material, comprising the following steps: mixing sodium pyrophosphate, dodecyl polyoxyethylene ether, polyether defoamer and water together, stirring for 30 minutes; then adding silica aerogel and propylene glycol methyl ether, stirring for 20 minutes; then adding nano-ceramic microbeads, vermiculite, chitosan / multi-layer carbon nanotube / ATO composite material, potassium silicate, styrene acrylic emulsion, polyether defoamer, stirring for 20 minutes; then adding hydroxymethyl cellulose and 0.5 mol / L ammonia aqueous solution, stirring evenly; the concentration of the ammonia is 0.5 mol / L. Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0012] The silicon-based thermal insulation material of the present invention has good thermal insulation performance by using acrylic emulsion, potassium silicate, nano-ceramic microbeads, vermiculite, silicon dioxide aerogel, chitosan / multi-layer carbon nanotubes / ATO composite material, and especially uses chitosan / multi-layer carbon nanotubes / ATO to improve the durability of the material. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0014] The polyether defoamer product model PPE-806 in the present invention is purchased from Jinan Xingfeilong Chemical; the silica aerogel is selected from commercially available products.
[0015] The following products were purchased from Sigma. The molecular weight of low molecular weight chitosan was 5000-190000 Da, and the molecular weight of high molecular weight chitosan was 310000-375000 Da. The average length of multilayer carbon nanotubes was 12 μm, the average diameter was 12 nm, and the surface area was 220 m 2 / g; single-walled carbon nanotubes are 300-500 μm long, 3-5 nm in average diameter, and have a surface area of 800-1000 m2 / g. The average particle size of ATO antimony tin oxide is <50 nm.
[0016] Example 1
[0017] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 8 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0018] The preparation method comprises the following steps: mixing 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water, and stirring for 30 minutes; then adding 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether, and stirring for 20 minutes; then adding 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 8 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion, and 0.3 parts of a polyether defoamer, and stirring for 20 minutes; then adding 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution, and stirring evenly.
[0019] The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is as follows: 400 mg of chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 100 mg of multi-layer carbon nanotubes and 60 mg of ATO are added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50° C. for 24 hours to obtain the chitosan; wherein the molecular weight of the chitosan is 310000-375000 Da.
[0020] Example 2
[0021] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 10 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L aqueous ammonia solution.
[0022] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 10 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and stirred evenly.
[0023] The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is the same as that in Example 1.
[0024] Example 3, a silicon-based thermal insulation material, comprising, by mass: 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 12 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoaming agent, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L aqueous ammonia solution.
[0025] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 12 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and the mixture is stirred evenly.
[0026] The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is the same as that in Example 1.
[0027] Example 4
[0028] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L aqueous ammonia solution.
[0029] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and the mixture is stirred evenly.
[0030] The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is the same as that in Example 1.
[0031] Example 5
[0032] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 16 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0033] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and the mixture is stirred evenly.
[0034] The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is the same as that in Example 1.
[0035] Comparative Example 1
[0036] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of low molecular weight chitosan / multilayer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0037] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of a low molecular weight chitosan / multilayer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and stirred evenly.
[0038] The preparation method of the low molecular weight chitosan / multilayer carbon nanotube / ATO composite material is as follows: 400 mg of low molecular weight chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 100 mg of multilayer carbon nanotubes and 60 mg of ATO are added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50°C for 24 hours to obtain; the molecular weight of the low molecular weight chitosan is 5000-190000 Da.
[0039] Comparative Example 2
[0040] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of low molecular weight chitosan / single-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0041] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of a low molecular weight chitosan / single-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and the mixture is stirred evenly.
[0042] The preparation method of the low molecular weight chitosan / single-layer carbon nanotube / ATO composite material is as follows: 400 mg of low molecular weight chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 100 mg of single-layer carbon nanotubes and 60 mg of ATO are added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50°C for 24 hours to obtain; the molecular weight of the low molecular weight chitosan is 5000-190000 Da.
[0043] Comparative Example 3
[0044] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of chitosan / single-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0045] The preparation method comprises the following steps: 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water are mixed together, and stirred for 30 minutes; 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether are added, and stirred for 20 minutes; 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of chitosan / single-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of a polyether defoamer are added, and stirred for 20 minutes; 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution are added, and the mixture is stirred evenly.
[0046] The preparation method of the chitosan / single-layer carbon nanotube / ATO composite material is as follows: 400 mg of chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 100 mg of single-layer carbon nanotubes and 60 mg of ATO are added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50°C for 24 hours to obtain; the molecular weight of the low molecular weight chitosan is 5000-190000 Da.
[0047] Comparative Example 4
[0048] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of chitosan / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L aqueous ammonia solution.
[0049] The preparation method comprises the following steps: mixing 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of polyether defoamer and 30 parts of water, and stirring for 30 minutes; then adding 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether, and stirring for 20 minutes; then adding 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of chitosan / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion and 0.3 parts of polyether defoamer, and stirring for 20 minutes; then adding 1 part of hydroxymethyl cellulose and 1 part of 0.5 mol / L ammonia aqueous solution, and stirring evenly.
[0050] The preparation method of the chitosan / ATO composite material is as follows: 400 mg of chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 60 mg of ATO is added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50°C for 24 hours to obtain; the molecular weight of the low molecular weight chitosan is 5000-190000 Da.
[0051] Comparative Example 5
[0052] A silicon-based thermal insulation material comprises, by mass, 70 parts of styrene-acrylic emulsion, 5 parts of potassium silicate, 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 7 parts of silica aerogel, 14 parts of multilayer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8 parts of propylene glycol methyl ether, 30 parts of water, 1 part of hydroxymethyl cellulose, and 1 part of 0.5 mol / L ammonia aqueous solution.
[0053] The preparation method comprises the following steps: mixing 0.5 parts of sodium pyrophosphate, 0.5 parts of dodecyl polyoxyethylene ether, 0.2 parts of a polyether defoamer and 30 parts of water, and stirring for 30 minutes; then adding 7 parts of silica aerogel and 8 parts of propylene glycol methyl ether, and stirring for 20 minutes; then adding 10 parts of nano-ceramic microbeads, 10 parts of vermiculite, 14 parts of multi-layer carbon nanotube / ATO composite material, 5 parts of potassium silicate, 70 parts of styrene-acrylic emulsion, and 0.3 parts of a polyether defoamer, and stirring for 20 minutes; then adding 1 part of hydroxymethyl cellulose and 1 part of a 0.5 mol / L ammonia aqueous solution, and stirring evenly.
[0054] The preparation method of the multilayer carbon nanotube / ATO composite material is as follows: 100 mg of multilayer carbon nanotubes and 60 mg of ATO are respectively added into 100 mL of 1% (V / V) acetic acid aqueous solution, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50°C for 24 hours to obtain the low molecular weight chitosan having a molecular weight of 5000-190000 Da.
[0055] Test Example 1
[0056] Thermal conductivity: Tested in accordance with the method specified in GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of insulating materials - Heat flow meter method".
[0057] Artificial weathering resistance test: Tested according to GBT / 9755-2014. A clean 150 mm×70 mm×6 mm cement board was coated with 1-2 mm 302 concrete interface agent, and then coated with 2 mm of the materials prepared in each embodiment and comparative example; the cement board was then cured and dried at room temperature for 7 days, and then the prepared test board was placed in a UV accelerated aging test chamber for testing, and the test board was observed for blistering, peeling, cracking, powdering and discoloration after 700 hours.
[0058] Table 1 Performance test.
[0059]
[0060] As can be seen from the data in Examples 1 to 5, with the increase of the content of chitosan / multi-layer carbon nanotubes / ATO composites, the thermal conductivity gradually decreases, and with the increase of the content, the magnitude of the decrease gradually decreases, showing good thermal insulation performance. The mechanical properties of the composite material can be strengthened by adding multi-layer carbon nanotubes, and chitosan strengthens the adsorption performance of the entire material, so that Examples 1-5 do not bubble, peel off, or crack in the artificial weathering resistance determination at 700h. High molecular weight chitosan, due to its longer molecular chain, can form a stronger flocculation network, and when preparing a composite material, it is easier to make ATO particles evenly dispersed. Multi-layer carbon nanotubes have a super high specific surface area due to structural characteristics, and are more suitable for doping ATO particles to obtain a composite material, so that it has better performance in the artificial weathering resistance determination.
Claims
1. A silicon-based thermal insulation material, characterized in that: The composition is composed of the following components by mass fraction: 70-80 parts of styrene-acrylic emulsion, 5-7 parts of potassium silicate, 10-12 parts of nano-ceramic microbeads, 10-12 parts of vermiculite, 7-9 parts of silica aerogel, 14-16 parts of chitosan / multi-layer carbon nanotube / ATO composite material, 0.5 parts of sodium pyrophosphate, 0.5 parts of polyether defoamer, 0.5 parts of dodecyl polyoxyethylene ether, 8-10 parts of propylene glycol methyl ether, 30-40 parts of water, 1-3 parts of hydroxymethyl cellulose, and 1-2 parts of 0.5 mol / L ammonia aqueous solution; the molecular weight of the chitosan is 310000-375000 Da; The preparation method of the chitosan / multi-layer carbon nanotube / ATO composite material is as follows: 400 mg of chitosan is dissolved in 100 mL of 1% (V / V) acetic acid aqueous solution; then 100 mg of multi-layer carbon nanotubes and 60 mg of ATO are added, and then ultrasonicated for 2 hours until the suspension becomes uniform, centrifuged, and dried at 50° C. for 24 hours to obtain the chitosan, wherein the molecular weight of the chitosan is 310,000-375,000 Da.
2. The silicon-based thermal insulation material according to claim 1, characterized in that: The multi-layer carbon nanotubes have an average length of 10 μm and an average diameter of 12 nm.
3. The silicon-based thermal insulation material according to claim 2, characterized in that: The average particle size of the ATO is <50 nm.
4. The silicon-based thermal insulation material according to any one of claims 1 to 3, characterized in that: The thermal conductivity of the silicon-based thermal insulation material is 0.0241-0.0243 Wm -1 K -1 .
5. The silicon-based thermal insulation material according to any one of claims 1 to 3, characterized in that: The silicon-based thermal insulation material does not bubble, peel or crack when subjected to an artificial weathering aging resistance test for more than 700 hours.
6. The method for preparing a silicon-based thermal insulation material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mix sodium pyrophosphate, dodecyl polyoxyethylene ether, polyether defoamer and water together and stir for 30 minutes; then add silica aerogel and propylene glycol methyl ether and stir for 20 minutes; then add nano-ceramic microbeads, vermiculite, chitosan / multi-layer carbon nanotube / ATO composite material, potassium silicate, styrene acrylic emulsion, polyether defoamer and stir for 20 minutes; then add hydroxymethyl cellulose and 0.5 mol / L ammonia aqueous solution and stir evenly.
7. The method for preparing silicon-based thermal insulation material according to claim 6, characterized in that: The concentration of the ammonia water is 0.5 mol / L.
Citation Information
Patent Citations
Waterborne heat-insulating slurry and preparation method thereof, as well as waterborne heat-insulating glass coating and preparation method thereof
CN106752237A
Inorganic silicon sound insulation and heat preservation gel and manufacturing method thereof
CN117229678A
Preparation method of coating with radiation and heat insulation functions
CN118064027A